Analisis Penggunaan Media Sosial Instagram dan Pengaruhnya Terhadap Business Performance Satisfaction (Studi Pada Pengusaha Kuliner Di Kota Malang) - Abdul Aziz; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The big number of social media users is a big appeal for entrepreneurs to find new customers and maintaining good relationship with them through social media. Not only big companies, small and medium enterprises (SMEs) also using social media to get some benefits, one of them is culinary SMEs. The number of culinary SMEs is raising rapidly, causing the competition between them get tougher. The present study explored the influences of social media technology use towards business performance satisfaction felt by SMEs. Beside trying to find out the influences between two things mentioned before, this research also considerating the two moderating effects provided by SMEs owners and/or employees' social competency and the intensity of sales generated from social media. The survey data were collected from 80 culinary SMEs in Malang City. The results from multiple linear regression analysis shows that regression model proposed has met the goodness of fit. Results also shows that SMEs whose used social media Instagram tended to report higher business performance satisfaction. Furthermore the social competency of owners and/or employees as independent variables also has influences to business performance satisfaction. Two moderating variables, social competency and the social media sales intensity also influences the relation between social media technology use and business performance satisfaction.